An updated enumeration of Bambusoideae in Central Highlands, Vietnam - Duy, Nong Van; Tran, Thai Vinh; Vu, Kim Cong; Dang , Thi Tham; Hoang, Thanh Truong; Tran , Van Tien (Academia Journal of Biology, 2023)
Bamboos are widely distributed in a variety of habitats in the Central Highlands. Different researchers treat species differently, leading to ambiguous reporting of generic and infrageneric taxa. Following extensive research, this paper is an updated enumeration report on the bamboos that have been found there. The result has recorded 29 species of bamboo belonging to 15 genera. The Bambusoideae grow naturally in almost all regions, in an altitudinal range that extends from 200 m up to 2,160 m. Bamboo in the Central Highlands is distributed in three vegetation types: degraded natural forests in valleys and mountain gorges, along rivers (twenty-one species); primary forest, mixed with broadleaved trees (six species); and dry dipterocarp forest (two species).